Boron as a contaminant at construction and demolition (C&D) debris landfills. (15th May 2020) - Xu, Rui; Gale, S. Adrian; Kim, Hwidong; Lott, Richard; Spreadbury, Chad J.; Laux, Steven; Townsend, Timothy G.
Highlights: Boron not typically a contaminant of potential concern at C&D debris landfills. Boron detected at 22 Florida C&D debris landfills; some above risk-based levels. Two sources were investigated: landfill leachate and site soils. Leaching tests performed on 19 materials prevalent in C&D debris landfills. Results suggest that the source of boron in groundwater is landfill leachate. Abstract: Elevated boron concentrations above the regulatory standard were inadvertently discovered in downgradient groundwater monitoring wells at 22 construction and demolition (C&D) debris landfills in Florida, US. This created a unique opportunity to evaluate whether C&D debris can be considered a plausible source of boron at unlined landfills. Approximately 1200 historical landfill-leachate and groundwater records were surveyed from semi-annual and annual monitoring reports covering a 9-year period. Laboratory leaching experiments were conducted on soils from each of these sites to determine if the source could have been boron mobilized from naturally occurring soils. Historical leachate quality data from lined landfills near four of the unlined C&D debris landfills were examined to determine if leachate from the unlined landfills could be the boron source. The US Environmental Protection Agency (EPA) Method 1312, or Synthetic Precipitation Leaching Procedure (SPLP), and the EPA Method 1316 were performed on materials commonly found in C&D debris to see if these products have the potential to leach appreciable levels of boron. The results of this work indicate leachate from unlined C&D debris landfills as the most plausible source of elevated boron concentrations in downgradient monitoring wells.